A novel scoring system for evaluating the difficulty of lysis of adhesion and surgical risk at repeat hepatectomy. (14th February 2020) - Kobayashi, Yuta; Shindoh, Junichi; Igata, Yu; Okubo, Satoshi; Hashimoto, Masaji
Abstract: Background: Repeat hepatectomy (ReHx) for recurrent hepatic malignancies reportedly provides oncological benefit for patients. However, severe adhesions at the time of ReHx may preclude safe and curative resection and there has been no reliable measure to estimate the surgical risk at ReHx. This study sought to create a new scoring system for evaluating the severity of adhesion after hepatectomy and tested its performance looking at the correlation with morbidity rate. Methods: Operative videos of 66 patients undergoing a second hepatectomy were reviewed and the difficulty levels in lysis of adhesion around the hepatic hilum (A score) and surrounding the liver (B score) were scored by two examiners and validated by two additional reviewers. Results: Very high interobserver agreement was confirmed between the two examiners ( κ value, 0.960‐0.963) and reproducibility of results were validated with weighted kappa values of >0.8 in both surgical resident and hepatobiliary surgeon. Linear correlation was confirmed between the difficulty score and postoperative morbidity rate. Multivariate analyses confirmed that previous cholecystectomy or transection of visceral surface of segment 4 or 5 was an independent factor predicting hard to extreme adhesions at the hepatic hilum regardless of the use of anti‐adhesion materials. Conclusions: The new difficulty scoring system for the lysis of adhesion at ReHx showed good interobserver agreement and reproducibility of the results. Given the strong correlation with postoperative morbidity rate, the present score could be used for evaluating the technical difficulties in ReHx and may offer a reliable measure for estimating the efficacy of anti‐adhesion materials in future analysis. Abstract : Highlight Repeat hepatectomy is generally technically demanding due to presence of adhesion after previous surgery. However, there have been no "measures" to adequately evaluate the severity of adhesion directly linked to the difficulty of surgery. This study sought to investigate the efficacy of a novel scoring system of adhesion for evaluating difficulty and risk of repeat hepatectomy.